PENANAMAN NILAI KEISLAMAN PADA ANAK DHUAFA DI PAUD INSAN CERDAS KOTA BEKASI - Khusniyati Masykuroh (EARLY CHILDHOOD : JURNAL PENDIDIKAN, 2020)
This study aims to find out an overview of the instilling of Islamic values ??on disadvantaged children, to find out the methods used in instilling Islamic values, to find out the obstacles and supports in instilling Islamic values, and to know the impact of instilling Islamic values ??for disadvantaged children at PAUD Insan Cerdas, Kota Bekasi. The method used in this study is a qualitative research by collecting data through observation, interviews, and documentation. Data analysis was carried out through three lines of data reduction, data presentation, and conclusion. As for the validity of the data, triangulation of various sources is used. The results of the study show that: 1) Instilling Islamic values ??on disadvantaged children at PAUD Insan Cerdas through four main components, they are: the introduction of faith, the practice of worship, morality, and the introduction of reading and short surah of the Qur'an; 2) The methods of instilling Islamic values ??used are storytelling, singing, playing, demonstrating, practicing, and answering question 3) The obstacles faced in instilling Islamic values ??are the parents background who had low education and low knowledge of Islam. While for the supports are the ‘Insan Cerdas Foundation’ and donors who care not only about children's education through Islamic curriculum programs, but also provide religious education for parents so they can synergize in instilling Islamic values ??at home and at school; 4) The impact of instilling Islamic values ??on disadvantaged children can be seen from the changes of their behavior : knowing Allah through their creations, behaving and saying well, helping each other and loving, being able to practice worship movements such as ablution, prayer, reading prayers, Hajj rituals, and knowing how to read and memorize short surah of Qur'an.